Effect of HAP decomposition on the corrosion behavior of Ti-HAP biocomposites - Toptan, Fatih (2018)
Ti-HAP biocomposites are gained attention for combining the attractive properties of Ti and hydroxyapatite (HAP). However, the decomposition of HAP at elevated processing temperatures is a major concern since it can lead to structural flaws and may deteriorate the corrosion resistance of Ti. The present study aims to investigate the corrosion behavior of Ti-HAP composite processed by powder metallurgy by performing potentiodynamic polarization and electrochemical impedance spectroscopy in 0.9wt% NaCl solution at body temperature. Results show that the presence of Ti lowers the HAP decomposition temperatures resulting in the formation of HAP-depleted zones acting as electrochemically active sites, decreasing the corrosion resistance.